2021
DOI: 10.1101/2021.12.17.21268008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fluvoxamine for Outpatient COVID-19 to Prevent Hospitalization: A Systematic Review and Meta-Analysis

Abstract: Importance: Widely available and affordable options for the outpatient management of COVID-19 are needed, particularly therapies that prevent hospitalization. Objective: Perform a meta-analysis of the available randomized clinical trial evidence for fluvoxamine in the outpatient management of COVID-19. Data Sources: World Health Organization International Clinical Trials Registry Platform and ClinicalTrials.gov. Study Selection: Completed outpatient trials with available results which compared fluvoxamine to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 15 publications
2
28
0
5
Order By: Relevance
“…Furthermore, there are currently 2 meta-analysis in a preprint state (Kacimi et al, 2021(Kacimi et al, , submitted 2021Lee et al, 2021Lee et al, , submitted 2021) and it should be noted that they did not include the same studies, only 2 studies in common on the 3 included studies. A meta-analysis has concluded that fluvoxamine has not shown significant efficacy in reducing either the mortality rates or mechanical ventilation while promising results in decreasing the likelihood for hospitalization in patients with COVID-19 (Kacimi et al, 2021(Kacimi et al, , submitted 2021.…”
Section: Current Evidence On Selective Serotonin Reuptake Inhibitors ...mentioning
confidence: 99%
“…Furthermore, there are currently 2 meta-analysis in a preprint state (Kacimi et al, 2021(Kacimi et al, , submitted 2021Lee et al, 2021Lee et al, , submitted 2021) and it should be noted that they did not include the same studies, only 2 studies in common on the 3 included studies. A meta-analysis has concluded that fluvoxamine has not shown significant efficacy in reducing either the mortality rates or mechanical ventilation while promising results in decreasing the likelihood for hospitalization in patients with COVID-19 (Kacimi et al, 2021(Kacimi et al, , submitted 2021.…”
Section: Current Evidence On Selective Serotonin Reuptake Inhibitors ...mentioning
confidence: 99%
“…Trials primarily enrolled unvaccinated adult outpatients at high risk for serious COVID-19 outcomes. 2 For pregnant patients, caution and obstetrical consultation are advised. Fluvoxamine is not recommended for pediatric patients.…”
Section: Children and Pregnant People Have Not Been Studiedmentioning
confidence: 99%
“…3 Fluvoxamine was generally well tolerated in the clinical trials Treatment was either 100 mg twice daily for 10 days, or started at 50 mg once daily, titrated to 100 mg twice daily over 2-3 days, and up to 3 times daily as tolerated for a total of 10-15 days. 2 Treatment ended without taper. 2 Patient-reported adverse events were similar in the fluvoxamine and placebo groups, and included mild headache and gastrointestinal symptoms.…”
Section: Children and Pregnant People Have Not Been Studiedmentioning
confidence: 99%
See 2 more Smart Citations